Cold Spray Parameters for White Portland Cement Coating on Stainless Steel - Jantasang, Auttachai; Laonapakul, Teerawat (Food Agricultural Sciences and Technology, 2019)
This research aims to study parameters that affect white Portland cement coating on 316L stainless steel using the cold spray technique in order to achieve 100-150 μm of coating thickness. The evaluation parameters, which were studied are: 1) speed of the sample moving pass through the spray nozzle 2) size of the spray nozzle 3) distance between the coating nozzle and sample surface 4) coating repetition. After the cold spray process, the thickness of the specimen was analyzed using an optical microscope. From preliminary experiments, the results showed that the nozzle of 1.2 mm with the speed of the sample moving pass through the nozzle of 600 cm/min produced good surface condition and satisfying distribution of coating area on coated sample. In addition, a distance between the nozzle of 20 cm with twice coating times, was the optimum condition created 132 μm of coating thickness of the coated sample.